Evaluation of Court Tennis Tennis Skills in Coached Athletes by Koni Aceh Province - Aldiansyah Akbar (Jurnal Serambi Ilmu, 2021)
This study aims to find out how the level of tennis skills in KONI Athletes in Aceh Province in 2018. This type of research can be classified as evaluation research. The population in this study was the Athletes of the Aceh Province KONI in 2018, totaling 8 people. While the sampling is done with the Total Sampling technique. The data collection technique used in this study is a test of service accuracy, three-minute rally and forehand and backhand drives. The results showed (1) a service accuracy test, (2) a three-minute rally test, (3) a forehand and backhand drive test. (4) the overall tennis skills test with the acquisition is categorized as moderate. Thus, the results of research and data analysis, it can be concluded that the tennis skills of the Aceh Province KONI Athletes in 2018 are in the medium category. In the sense that the results of education carried out by the Aceh Province KONI in 2018 have not obtained maximum results.